Differential Effects of Biomimetic Thymine Dimers and Corresponding Photo-Adducts in Primary Human Keratinocytes and Fibroblasts - Rosanna Monetta; Denise Campagna; Valeria Bartolocci; Alessio Capone; Massimo Teson; Silvia Filippi; Sofia Gabellone; Davide Piccinino; Raffaele Saladino; Elena Dellambra (Biomolecules)
UVB radiation induces DNA damage generating several thymine photo-adducts (TDPs), which can lead to mutations and cellular transformation. The DNA repair pathways preserve genomic stability by recognizing and removing photodamage. These DNA repair side products may affect cellular processes. We previously synthesized novel thymine biomimetic thymine dimers (BTDs) bearing different alkane spacers between nucleobases. Thus, the present study investigates whether novel BTDs and their TDPs can modulate DNA damage safeguard pathways of primary keratinocytes and fibroblasts using 2D and 3D models. We found that the p53/p21waf1 pathway is activated by BTDs and TDPs in primary cells similar to UVB exposure. Compound 1b can also induce the p53/p21waf1 pathway in a 3D skin model. However, BTDs and TDPs exhibit distinct effects on cell survival. They have a protective action in keratinocytes, which maintain their clonogenic ability following treatments. Conversely, compounds induce pro-apoptotic pathways in fibroblasts that exhibit reduced clonogenicity. Moreover, compounds induce inflammatory cytokines mainly in keratinocytes rather than fibroblasts. Matrix metalloproteinase 1 is up-regulated in both cell types after treatments. Therefore, BTDs and TDPs can act in the short term as safeguard mechanisms helping DNA damage response. Furthermore, they have distinct biological effects depending on photodamage form and cell type.